1994
DOI: 10.1136/jnnp.57.12.1479
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose metabolism in neurofibromatosis type 1 assessed with [18F]-2-fluoro-2-deoxy-D-glucose and PET.

Abstract: Cerebral PET with [18FJ-2-fluoro-2-deoxy-D-glucose has been performed in four patients with neurofibromatosis type 1 (NF1) to assess the relation between cerebral metabolic activity, MRI, and the presence of neurological symptoms, including seizures, as well as mental and language retardation. Widespread hypometabolism occurred in three of the patients. The lesions on MRI, which were localised in the subcortical white matter and grey structures, had normal rates of glucose metabolism. This finding suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
6
18
0
Order By: Relevance
“…Balestri et al previously suggested that UBOs and hypometabolism in brain PET images were independent and distinctive features of NF1 because metabolic activity was normal in areas that appeared to be abnormal on MRI. 10) Our study findings are consistent with their report, and we reproduced their findings in a relatively large number of subjects (75 patients). To further clarify the role of UBOs and thalamic glucose hypometabolism in NF1, a prospective longitudinal study with a larger number of subjects and with systemic assessment of neuropsychological function is required.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Balestri et al previously suggested that UBOs and hypometabolism in brain PET images were independent and distinctive features of NF1 because metabolic activity was normal in areas that appeared to be abnormal on MRI. 10) Our study findings are consistent with their report, and we reproduced their findings in a relatively large number of subjects (75 patients). To further clarify the role of UBOs and thalamic glucose hypometabolism in NF1, a prospective longitudinal study with a larger number of subjects and with systemic assessment of neuropsychological function is required.…”
Section: Discussionsupporting
confidence: 93%
“…A hypometabolic pattern has been reported in several studies of brain PET images of patients with NF1. 9,10) Therefore, it is possible that there is a relationship between cerebral hypometabolism and cognitive impairment in patients with NF1. 10) North et al suggested that the pathogenesis of the neurological deficit in patients with NF1 was as follows:…”
Section: Discussionmentioning
confidence: 99%
“…36 A study of 20 adults with NF-1 also showed reduced FDG-PET metabolism in the thalamus, and to a lesser degree, in the cerebellum. In these studies, the extent of abnormal cerebral metabolism did not correlate with the presence or number of UBOs, 35,37 degree of cognitive impairment, 35 or differences in age or sex, 37 similar to the present study.…”
supporting
confidence: 85%
“…Prior FDG-PET studies in NF-1 [35][36][37] have shown abnormal cerebral metabolism similar in distribution to the perfusion pattern noted in this study, for example, global hypometabolism with a more marked hypometabolism in the posterior brain regions. For example, in 4 adolescents with NF-1 (9 -20 years of age), global hypometabolism with a more marked reduction of FDG activity in the thalamus and the occipital lobes was noted with intact metabolism in the striatum.…”
supporting
confidence: 79%
See 1 more Smart Citation